Producing global media memories: Media events and the power dynamics of transnational television history. (June 2017) - Lundgren, Lars; Evans, Christine E
The 1960s witnessed the emergence of television as a global medium. One way of demonstrating the powers and possibilities of television was the production and airing of transnational broadcast events. In order to produce these, national broadcast organizations had to engage in joint production of such events. The article examines two such events: Gagarin's return to Moscow after orbiting the earth in April 1961 and the more well-known 'Our World' broadcast 6 years later. At the time of their production, these broadcasts were seen as crucial moments in television history, as prototypes of what could be expected of television in the future. They also relied on extensive cooperation between broadcast organizations in socialist and Western countries, organizations that to a large extent shared the same production values but also had to negotiate competing visions of the geography of modern communications networks. The broadcasts discussed in this article thus provide the opportunity to reflect upon the shaping of television history and global media memories. Based on case studies of the planning and production of the broadcasts, the article argues that global power relations have shaped the remembered history of television and therefore must be part of our understanding of it.